2018
DOI: 10.1136/archdischild-2018-315060
|View full text |Cite
|
Sign up to set email alerts
|

Drug monitoring in long-term treatment with adalimumab for juvenile idiopathic arthritis-associated uveitis

Abstract: AAA-associated LOR frequently occurs in long-term treatment with ADA for JIA-associated uveitis. Concomitant immunosuppressive therapy significantly reduces the risk of LOR due to AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 15 publications
6
36
0
Order By: Relevance
“…Concomitant use of methotrexate has a protective role against the development of adalimumab ADA [risk ratio 0.33; 95% Confidence interval (95% CI) 0.21, 0.52] (Doeleman et al, 2019). The above findings regarding adalimumab were also reported in relation to patients receiving this drug for JIAassociated uveitis (Skrabl-Baumgartner et al, 2019). In addition, the risk of infusion reactions in patients treated with tocilizumab, infliximab or rilonacept increased in the presence of ADA (Ruperto et al, 2007;Lovell et al, 2013;Yokota et al, 2014).…”
Section: Therapeutic Drug Monitoring and Anti-drug Antibodies As Biomarkers Of Efficacy And Toxicity Of Biologic Treatments In Jiamentioning
confidence: 89%
“…Concomitant use of methotrexate has a protective role against the development of adalimumab ADA [risk ratio 0.33; 95% Confidence interval (95% CI) 0.21, 0.52] (Doeleman et al, 2019). The above findings regarding adalimumab were also reported in relation to patients receiving this drug for JIAassociated uveitis (Skrabl-Baumgartner et al, 2019). In addition, the risk of infusion reactions in patients treated with tocilizumab, infliximab or rilonacept increased in the presence of ADA (Ruperto et al, 2007;Lovell et al, 2013;Yokota et al, 2014).…”
Section: Therapeutic Drug Monitoring and Anti-drug Antibodies As Biomarkers Of Efficacy And Toxicity Of Biologic Treatments In Jiamentioning
confidence: 89%
“…The timing of adalimumab ADA development is controversial: in some adult studies ADA prevalence did not increase with treatment duration, 53 , 54 while in other studies there was a significant increase, with ADA developing between 4.5 months and 12 months of treatment. 9 , 34 , 44 , 50 , 52 , 55 Similarly, studies in JIA showed both trends: a significant increase of ADA with time 35 or no correlation with treatment duration, 30 suggesting that ongoing monitoring to establish their clinical relevance and impact on management is required.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 30 In JIA, it was noted that transient ADAs (defined as measurable ADAs on up to two consecutive time points which disappeared on subsequent measurements without having any impact on treatment efficacy of toxicity) were not associated with diminished response to medication, whereas permanent ADAs did lower treatment response. 34 …”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-alpha blockers (adalimumab and infliximab) are the most commonly used biologic agents in JIA-associated uveitis, and these agents have markedly improved the visual prognosis of the disease. 5,6 However, some patients fail to respond to different immunomodulators, including conventional agents and the more potent biologics, or they are intolerant to these therapies. In this subset of patients, signs of chronic low-grade inflammation and flare in the anterior chamber may persist despite aggressive systemic immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 99%